Influence of FFF process parameters and macrostructure homogeneity on PLA impact strength - Bączkowski, Michał; Marciniak, Dawid; Bieliński, Marek (Polimery, 2021)
The article presents studies of the additive manufacturing printing parameters influence on the impact strength of PLA samples obtained by the fused filament fabrication (FFF) method. Two process variables were taken into account in the research program: the height of the printed layer and the printing temperature. An optical microscope was used to analyze the cross-section image (breakthrough) of the samples. The impact strength was determined at −40°C and 23°C. Selected geometric features of the macrostructure (uniformity and thickness of individual layers, voids) determined on the basis of the sample cross-section image analysis, enhanced the possibility of assessing the PLA impact strength, depending on the adopted process variables and the temperature at which the experiment was carried out.